CAPILLARY BLOOD GLUCOSE POINT OF CARE TESTING FOR CLINIC SCREENING: BENEFICIAL OR WASTAGE - A, Noorhidayah; S, Norhaslinda; S, Chee Keong (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Glycated haemoglobin (HbA1c) and home blood glucose monitoring are the recommended tools for assessing glycemic control among patients with diabetes. However, health clinics and hospitals are still utilising capillary blood glucose point of care testing (CBG POCT) either as clinic routine screening or for assessment of patients. The accuracy and benefits of this CBG POCT is doubtful and a potential waste. METHODOLOGY This study aimed to determine the clinical relevance of CBG POCT in detecting symptomatic hypoglycaemia or hyperglycaemia during clinic visit and its correlation with HbA1c. This was a cross-sectional study conducted for 1 month that included all patients attending diabetes clinic in Hospital Sultan Haji Ahmad Shah Temerloh. All CBG POCT data were collected and corresponding fasting blood sugar (FBS) and HbA1c were retrieved from patient information system. RESULTS 97 patients (mean age 49.4±16.3 years) were included with mean CBG POCT 11.6±4.5 mmol/L. All CBG were post-prandial glucose. Only 2% (n=2) of patients had hypoglycaemia (CBG<4 mmol/L) and 17.5% (n=17) had markedly elevated CBG (>15 mmol/L). All of these patients were asymptomatic. 90% (n=87) of patients who attended clinic had HbA1c taken. Mean HbA1c was 9.6±2.5% and 50% had HbA1c above 10%. However CBG POCT did not correlate with patient’s recent HbA1c. CONCLUSION CBG POCT did not reliably reflect glycemic control of patients and was influenced by postprandial variability. Most patients attending clinic already had HbA1c and FBS taken prior to clinic visit. This reflects a wastage in clinical practice. In general, cessation of CBG POCT in government practice would reduce cost of RM540/year (RM0.45 per test). Additionally cessation of CBG POCT would reduce screening time and prevent unnecessary needle stick injury. Capillary blood glucose use in clinic screening is a waste and not justified in both clinical value and cost.